Cytokine-armed pyroptosis induces antitumor immunity against diverse types of tumors - Sara Orehek; Taja Železnik Ramuta; Duško Lainšček; Špela Malenšek; Martin Šala; Mojca Benčina; Roman Jerala; Iva Hafner-Bratkovič (Nature Communications)
Abstract Inflammasomes are defense complexes that utilize cytokines and immunogenic cell death (ICD) to stimulate the immune system against pathogens. Inspired by their dual action, we present cytokine-armed pyroptosis as a strategy for boosting immune response against diverse types of tumors. To induce pyroptosis, we utilize designed tightly regulated gasdermin D variants comprising different pore-forming capabilities and diverse modes of activation, representing a toolbox of ICD inducers. We demonstrate that the electrogenic transfer of ICD effector-encoding plasmids into mouse melanoma tumors when combined with intratumoral expression of cytokines IL-1β, IL-12, or IL-18, enhanced anti-tumor immune responses. Careful selection of immunostimulatory molecules is, however, imperative as a combination of IL-1β and IL-18 antagonized the protective effect of pyroptosis by IFNγ-mediated upregulation of several immunosuppressive pathways. Additionally, we show that the intratumoral introduction of armed pyroptosis provides protection against distant tumors and proves effective across various tumor types without inducing systemic inflammation. Deconstructed inflammasomes thus serve as a powerful, tunable, and tumor-agnostic strategy to enhance antitumor response, even against the most resilient types of tumors.